2015
DOI: 10.1371/journal.pone.0129372
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor (TNF) –308G>A, Nitric Oxide Synthase 3 (NOS3) +894G>T Polymorphisms and Migraine Risk: A Meta-Analysis

Abstract: Background and ObjectiveConflicting data have been reported on the association between tumor necrosis factor (TNF) –308G>A and nitric oxide synthase 3 (NOS3) +894G>T polymorphisms and migraine. We performed a meta-analysis of case-control studies to evaluate whether the TNF –308G>A and NOS3 +894G>T polymorphisms confer genetic susceptibility to migraine.MethodWe performed an updated meta-analysis for TNF –308G>A and a meta-analysis for NOS3 +894G>T based on studies published up to July 2014. We calculated stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…( 10) There is a relationship between the presences of the gene NOS3 Single-nucleotide polymorphism T-786 (SNP T-786) with the occurrence of preeclampsia. (14) This could be elucidated if a further study was done in this study subjects to examine the association between NOS3 gene/ polymorphism of the NOS3 gene, NOS3 enzyme level, L-citrulline level, and blood pressure. If those studies were also proven to be wrong, it could be concluded that the main etiopathogenesis of preeclampsia in this study subjects was not due to vascular factor.…”
Section: Discussionmentioning
confidence: 96%
“…( 10) There is a relationship between the presences of the gene NOS3 Single-nucleotide polymorphism T-786 (SNP T-786) with the occurrence of preeclampsia. (14) This could be elucidated if a further study was done in this study subjects to examine the association between NOS3 gene/ polymorphism of the NOS3 gene, NOS3 enzyme level, L-citrulline level, and blood pressure. If those studies were also proven to be wrong, it could be concluded that the main etiopathogenesis of preeclampsia in this study subjects was not due to vascular factor.…”
Section: Discussionmentioning
confidence: 96%
“…Despite denying an overall association between this polymorphism and migraine risk, subgroup analyses demonstrated, in line with previous results, that the ‘A’ allele of the TNF -308G>A variant increases the risk of migraine among non-Caucasians (pooled OR = 1.82). Moreover, the risk for MA was slightly increased among both Caucasians and non-Caucasians [ 43 ].…”
Section: Genetic Findings Related To the Immune System In Migraineursmentioning
confidence: 99%
“…[ 16 ] A recent meta-analysis indicated that “T” allele of the eNOS +894G > T variant increased the risk of migraine among non-Caucasians. [ 17 ] The substitution of thymine by cytosine in the 5′ promoter region at nucleotide—786 (−786T>C) results in a significant reduction in eNOS gene promoter activity and in decreased basal NO production. [ 16 ] Similarly, there are some controversies for the connection between eNOS polymorphism (−786T>C) and migraine risk.…”
Section: Introductionmentioning
confidence: 99%